Healing Hearts Together — an emotionally focused intervention for couples after a cardiac event: a randomized controlled trial protocol - Tulloch, Heather E.; Greenman, Paul S.; Reed, Jennifer; Susinski, Stephanie; Kasos, Eniko; Tasca, Giorgio A.; Mielniczuk, Lisa; Wells, George; Sun, Louise Y.; Johnson, Susan M. (Frontiers in Psychology, 2025)
IntroductionCouple relationships are important for health. Relationship distress is associated with increased incident and prognostic cardiovascular risk, while positive support is linked to heart-healthy behaviors and improved outcomes. This paper describes the study rationale, objectives, design, and methods of the Healing Hearts Together (HHT) randomized controlled trial (RCT).ObjectivesThe primary objective is to examine the difference in relationship quality between the 8-week HHT intervention group and usual care (UC) at program completion. Secondary objectives include evaluating the impact of HHT on relationship quality at 6 months, and mental health, quality of life, and cardiovascular risk factors measured at 8 weeks and 6 months post-intervention, as compared to usual care.MethodsPatients and their partners are recruited within 6 months of a cardiac event, procedure, or hospitalization and randomized 1:1 to HHT or UC. Assessments occur at baseline, 8 weeks, and 6 months follow-up. Analyses are planned as intention-to-treat, with multi-level analyses of covariance (ANCOVA) for the primary outcome: 8-week relationship quality as measured by the Dyadic Adjustment Scale. Secondary objectives will be evaluated using multi-level modeling for repeated measures.Anticipated resultsIt is expected that participants randomized to HHT will report higher relationship quality and improved secondary outcomes than will participants in UC.ConclusionAs the first study to evaluate a relationship-enhancement program for couples with cardiac disease, findings will have important clinical implications regarding the effect of relationship interventions on heart health.